Pengaruh Gaji, Stres Kerja, dan Keadilan Interaksional terhadap Perilaku Penyimpangan Pegawai (Employee Deviance) Studi Kasus terhadap Divisi Marketing PT. XYZ - Deni Wardani; Yousef Yousef (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
With the high expectation towards quality human resouce. This research was conducted to identify the effect of Wage Compensation, Interactional Justice and Job Stres towards Employee Deviance. The object of this research is PT. XYZ which is one of the most respectable company in Indonesia. This research is a quantitative descriptive research. There were 149 respondents  of  XYZ’s  Marketing  Division  which  were  gathered  by  convenience sampling. The results showed that Wage Compensation, Job Stres, and Interactional Justice has a significant effect towards Employee Deviance.